Copper oxide-graphite composite material, extraction method, negative electrode, battery and power-related equipment

By detecting the battery health status screening and disassembly processing of decommissioned lithium batteries, combined with calcining treatment, the extraction of copper oxide graphite composite materials was successfully achieved, solving the problems of complex graphite recycling processes, high costs and environmental pollution in the existing technology, and achieving a simple process, low cost and pollution-free graphite recycling effect.

CN119560668APending Publication Date: 2025-03-04BOTREE CYCLING SCI &TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411720791.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

The graphite recycling technology in existing lithium-ion batteries has problems such as complex process flow, high cost, and environmental pollution, and lacks a graphite recycling process with simple process, low cost and pollution-free.

Method used

The cells that meet the preset copper doping conditions were screened by detecting the battery health status of the decommissioned lithium batteries, and the pre-regeneration graphite powder was obtained by dismantling and separation. The copper oxide graphite composite material was obtained by calcining.

Benefits of technology

The graphite recycling process is simple, low cost and pollution-free, suitable for large-scale industrial applications, improves the electrochemical performance of recycled graphite, and solves the problems of loss of the graphitization degree, low reversible specific capacity, low first charge and discharge efficiency, and poor cycle stability of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119560668A_ABST
    Figure CN119560668A_ABST
Patent Text Reader

Abstract

The invention provides a copper oxide graphite composite material and an extraction method thereof, a negative electrode, a battery and power-related equipment, and relates to the technical field of battery recovery. The extraction method comprises the following steps: detecting a target retired lithium battery to obtain a battery health state result; screening the target retired lithium batteries, and disassembling and separating the batteries meeting a preset copper doping condition to obtain graphite powder before regeneration; and calcining the graphite powder before regeneration to obtain the copper oxide graphite composite material. Compared with a conventional graphite recycling and regenerating means, the method has the advantages that the waste graphite does not need to be leached, the use of acid and alkali is omitted, the material performance does not need to be improved through repeated high-temperature calcination, impurity removal and carbon coating, and the method is simple in process, low in cost, free of pollution, high in universality and suitable for large-scale industrial application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of battery recycling, and in particular to a copper oxide graphite composite material and an extraction method, a negative electrode, a battery and electrical equipment. Background Art

[0002] Lithium-ion batteries have been widely used in new energy vehicles, portable electronic products, energy storage power stations and other fields due to their advantages such as high energy density, long cycle life and low self-discharge rate. Graphite, as an ideal anode material in lithium-ion batteries, accounts for 12% to 21% of the battery weight and 8% to 15% of the battery cost due to its excellent cycle stability and rate capability. With the popularity of electric vehicles and portable electronic products, the number of discarded lithium-ion batteries generated each year has increased dramatically, which not only puts pressure on the limited supply of resources, but also consumes a large amount of petroleum resources, exacerbating energy and environmental problems. Therefore, the recycling and reuse of graphite in lithium-ion batteries has become an urgent problem that needs to be solved.

[0003] At present, the recycling process of waste graphite in lithium-ion batteries mainly includes two stages: impurity removal and carbon coating repair. Some technologies can obtain high-quality graphite materials through acid washing purification, oxidation removal of cracked carbon, and carbon source coating, but a large amount of acid is used in the process, resulting in a large amount of waste liquid, which pollutes the environment. Other technologies remove impurities through steps such as water washing, acid leaching, and high-temperature treatment. Although they can repair graphite materials, the process is cumbersome and the processing cost is high, which is not suitable for industrial recycling. In addition, there are technologies that use biological enzyme liquid and composite acid liquid modification treatment, and then silicon composite and carbon coating methods. Although they can improve material performance, the process is complicated, which increases the process cost and implementation difficulty.

[0004] Although these technologies can improve the performance of graphite materials to a certain extent, they generally have problems such as complex process flow, high cost, and environmental pollution. For example, although some processes can obtain high-quality graphite, these technologies have not been implemented on a large scale industrially due to cost issues. In addition, some studies have used hydrothermal + chemical precipitation, solid phase method, molten salt method and other technical means to recycle materials such as lithium iron phosphate. Although these methods are effective, they also face problems such as high processing costs, high energy consumption, and possible secondary pollution. For graphite materials, high-temperature reduction method, high-temperature cracking method, mechanochemical method, etc., although the process is simple and efficient, the energy consumption is high and toxic and harmful gases may be produced. Although the hydrometallurgical method has the advantages of high efficiency, reliable operation, and low energy consumption, a large amount of corrosive reagents are used during the operation, which not only makes wastewater treatment complicated, but also requires a corresponding increase in treatment costs.

[0005] In summary, the existing recycling technology still lacks a graphite recycling process with simple process, low cost and no pollution. Although most processes can obtain high-quality graphite, these technologies have not been implemented on a large scale due to cost issues. If a simple and easy graphite regeneration method can be provided and high-quality battery-grade materials can be obtained by using this method, it will have a very positive and important significance for the development of the new energy industry and environmental protection.

[0006] In view of this, the present invention is proposed. Summary of the invention

[0007] The purpose of the present invention is to provide a copper oxide graphite composite material and an extraction method, a negative electrode, a battery and electrical equipment. The copper oxide graphite composite material extraction method has the advantages of simple process, low cost, no pollution, high universality, and suitability for large-scale industrial application.

[0008] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:

[0009] In a first aspect, the present invention provides a method for extracting a copper oxide graphite composite material, comprising:

[0010] Detecting a target retired lithium battery to obtain a battery health status result corresponding to the target retired lithium battery;

[0011] The target retired lithium batteries are screened by using the battery health status results as the copper doping level, and the target retired lithium batteries whose battery health status meets the preset copper doping conditions are disassembled and separated to obtain graphite powder before regeneration;

[0012] The graphite powder before regeneration is calcined to obtain a copper oxide graphite composite material.

[0013] In an optional implementation, the method for detecting the battery health status result includes:

[0014] Detecting the target retired lithium battery to obtain the battery internal resistance of the target retired lithium battery at the end of its battery life and the internal resistance of the battery in a current state;

[0015] Calculate the battery health status result corresponding to the target retired lithium battery according to the battery internal resistance at the end of battery life and the internal resistance of the battery in the current state, as well as the internal resistance of the target retired lithium battery when it leaves the factory;

[0016] In an optional implementation, the calculation expression of the battery health status result is:

[0017]

[0018] Wherein, SOH represents the battery health status result; R EOL Represents the internal resistance of the battery at the end of its life; R BOL represents the internal resistance of the battery when it leaves the factory; R represents the internal resistance of the battery in its current state.

[0019] In an optional embodiment, the target retired lithium batteries are screened by using the battery health status result as the copper doping level, and the target retired lithium batteries whose battery health status meets the preset copper doping conditions are disassembled and separated to obtain graphite powder before regeneration, including:

[0020] Obtaining the battery health status result of the target retired lithium battery;

[0021] Determining whether the battery health status result meets the preset copper doping condition;

[0022] If yes, the target retired lithium battery meeting the preset copper doping condition is disassembled and separated to obtain the graphite powder before regeneration;

[0023] In an optional embodiment, the preset copper doping condition is: 65%≤SOH≤80%; wherein SOH represents the battery health status result of the target retired lithium battery;

[0024] In an optional embodiment, if the target retired lithium battery is a lithium cobalt oxide battery or a ternary lithium battery, the preset copper doping condition is: 75%≤SOH≤80%;

[0025] In an optional implementation, if the target retired lithium battery is a lithium iron phosphate battery, the preset copper doping condition is: 65%≤SOH≤80%.

[0026] In an optional implementation manner, after determining whether the battery health status result meets the preset copper doping condition, the method further includes:

[0027] If not, the following processing is performed according to the battery health status result of the target retired lithium battery:

[0028] If the battery health status result is greater than the maximum value of the preset copper doping condition, the target retired lithium battery is pre-processed, and the step of returning to execute the step of detecting the target retired lithium battery to obtain the battery health status result corresponding to the target retired lithium battery;

[0029] If the battery health status result is lower than the minimum value of the preset copper doping condition, the target retired lithium battery is subjected to harmless treatment.

[0030] In an optional embodiment, the pre-treatment includes at least one of charge-discharge cycle treatment, reverse charge treatment, over-discharge <1.2V treatment and short-circuit treatment.

[0031] In an optional embodiment, the disassembly and separation process includes:

[0032] Disassembling the target retired lithium battery to obtain graphite negative electrode sheets; or crushing and sorting the target retired lithium battery to obtain negative electrode graphite powder;

[0033] The graphite negative electrode sheet or the negative electrode graphite powder is subjected to solvent washing treatment to obtain the graphite powder before regeneration.

[0034] In an optional embodiment, the solvent used in the solvent washing treatment includes at least one of water, carbonate solvents, organic ether solvents and N-methylpyrrolidone.

[0035] In an optional embodiment, the sorting process includes at least one of gravity sorting, magnetic separation and flotation.

[0036] In an optional embodiment, the calcining of the graphite powder before regeneration to obtain the copper oxide graphite composite material comprises:

[0037] The graphite powder before regeneration is subjected to calcination treatment, airflow classification, demagnetization treatment and material mixing treatment respectively under air atmosphere to obtain the copper oxide graphite composite material;

[0038] In an optional embodiment, the calcination temperature of the calcination treatment is 450°C to 800°C;

[0039] In an optional embodiment, the calcination time of the calcination treatment is 1 hour to 2 hours.

[0040] In a second aspect, the present invention provides a copper oxide graphite composite material, which is prepared by the copper oxide graphite composite material extraction method as described in any one of the above embodiments;

[0041] In an optional embodiment, the copper content in the copper oxide graphite composite material is less than 3%.

[0042] In a third aspect, the present invention provides a copper oxide-graphite composite material, which is prepared by the copper oxide-graphite composite material extraction method as described in the above embodiment.

[0043] In a fourth aspect, the present invention provides a negative electrode, wherein the negative electrode comprises a negative electrode material;

[0044] The negative electrode material is the copper oxide graphite composite material as described in the above embodiment.

[0045] In a fifth aspect, the present invention provides a battery comprising the negative electrode as described in the above embodiment.

[0046] In a sixth aspect, the present invention provides an electrical device, comprising a battery as described in the above embodiment.

[0047] The present invention utilizes the in-situ electrochemical doping of nano-copper inside graphite during the battery charging and discharging process, obtains nano-copper-doped graphite powder through refined disassembly and effective separation, eliminates the use of acid and alkali, and then performs a one-step oxidation calcination regeneration to obtain a novel copper oxide-graphite composite material, effectively improves the electrochemical performance of the regenerated graphite without destroying the graphite structure, has a simple process, and solves the problems of large graphitization degree loss, low reversible specific capacity, low initial charge and discharge efficiency, and poor cycle stability of the regenerated graphite recovered from the current lithium ion battery.

[0048] In summary, compared with conventional graphite recycling and regeneration methods, the present invention does not require leaching treatment of waste graphite, eliminates the use of acid and alkali, and does not require repeated high-temperature calcination to remove impurities and carbon to improve material properties. It has a simple process, low cost, no pollution, high universality, and is suitable for large-scale industrial applications. BRIEF DESCRIPTION OF THE DRAWINGS

[0049] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0050] Figure 1 This is a schematic diagram of the process of extracting the copper oxide graphite composite material in an embodiment of the present application;

[0051] Figure 2 The XRD pattern of the copper oxide graphite composite material in Example 1 of the present application (including before regeneration);

[0052] Figure 3 This is a SEM image of the copper oxide graphite composite material in Example 1 of the present application;

[0053] Figure 4 This is the XRD diagram of the copper oxide graphite composite material in Comparative Example 1 of the present application. DETAILED DESCRIPTION

[0054] The embodiments of the present invention will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. If no specific conditions are specified in the examples, the conditions are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be obtained commercially.

[0055] refer to Figure 1 In an embodiment of the present application, a method for extracting a copper oxide graphite composite material is provided, comprising:

[0056] Step S1, detecting a target retired lithium battery to obtain a battery health status result corresponding to the target retired lithium battery.

[0057] As mentioned above, the target retired lithium batteries are waste lithium-ion batteries that need to be regenerated, recovered and extracted by the copper oxide graphite composite material in the method of this embodiment. In the case of over-discharge or battery aging, especially when the voltage drops below a certain level, the copper ions on the copper foil may dissolve from the negative electrode into the electrolyte and migrate to other places inside the battery to redeposit, resulting in the precipitation of negative electrode copper. This phenomenon usually occurs in lithium-ion batteries and is a problem that needs special attention and treatment in the copper oxide graphite composite material extraction method of this embodiment. In this step, the retired lithium battery is tested for the state of health (SOH) to evaluate the performance and remaining life of the battery, thereby obtaining the SOH result of the battery, which reflects the state of the battery relative to a new battery.

[0058] Through SOH testing, batteries suitable for further processing can be screened out, avoiding ineffective or costly treatment of batteries in poor condition.

[0059] Specifically, battery testing equipment can be used to measure the internal resistance, voltage, capacity and other parameters of the battery, and the SOH value can be obtained by comparing them with the factory parameters.

[0060] Step S2, using the battery health status result as the copper doping level to screen the target retired lithium batteries, and disassembling and separating the target retired lithium batteries whose battery health status meets the preset copper doping conditions to obtain graphite powder before regeneration.

[0061] In this step, the battery health status result is used as the copper doping level corresponding to the retired lithium battery, so that there is no need to test the copper content of each battery. Instead, the various electrochemical variables in the simple SOH result can be detected and calculated, and then the batteries that meet the preset copper doping conditions can be intuitively screened out only through the SOH result. The screened batteries that meet the conditions are suitable for graphite and copper recovery, and the batteries suitable for disassembly are selected. These batteries usually have a better internal structure and a copper content that is more suitable for recycling.

[0062] Through screening, it can be ensured that only batteries with higher value are further processed, improving resource utilization efficiency.

[0063] Specifically, a SOH threshold may be set, and only batteries with a SOH value higher than the threshold will proceed to the next step.

[0064] The screened batteries are then disassembled to separate the graphite negative electrode sheets or negative electrode graphite powder, thereby obtaining the graphite powder before regeneration, which is the basic material for subsequent processing.

[0065] The disassembly and separation process provides raw materials for further processing of graphite and doping of copper oxide, while reducing the impact of waste batteries on the environment.

[0066] Mechanical disassembly equipment can be used to disassemble the battery and extract the graphite negative electrode material.

[0067] Step S3, calcining the graphite powder before regeneration to obtain a copper oxide graphite composite material.

[0068] As described above, the graphite powder before regeneration is calcined in an air atmosphere to remove impurities and dope nano copper, thereby obtaining a copper oxide-graphite composite material, which has higher electrochemical properties.

[0069] The calcination treatment not only removes impurities on the graphite surface, but also improves the electrochemical properties of the material by in-situ doping with nano-copper oxide.

[0070] Calcination can be carried out under controlled temperature and time conditions to ensure the doping effect. During the calcination process, the carbon on the surface of the graphite reacts with oxygen in the air to produce carbon dioxide.

[0071] Through calcination, the structure of graphite is stabilized, and the doping of nano copper oxide improves the conductivity and electrochemical activity of the material. The use of harmful chemicals is avoided throughout the process, while efficient recycling of graphite and copper from waste batteries is achieved, reducing the impact on the environment. By screening and optimizing the processing flow, unnecessary processing steps are reduced, the overall cost is reduced, and the performance of the material is improved, increasing its market value.

[0072] It should be noted that copper oxide, as a negative electrode material for lithium-ion batteries, has a high theoretical capacity (670 mAh g -1 ), which is nearly twice that of commercial graphite negative electrodes, which means that in theory, using copper oxide as a negative electrode material can store more lithium ions, thereby increasing the capacity of the battery. Moreover, copper oxide is considered to be a safe, low-cost and environmentally friendly material. This is related to its chemical stability and relatively abundant resources, which makes it have potential economic and environmental advantages in battery materials.

[0073] Although copper oxide has a high theoretical capacity, it performs poorly in terms of electrochemical activity. During the charge and discharge cycle of the battery, copper oxide undergoes significant volume expansion and contraction, causing the active material to break up, which can rapidly reduce the battery's capacity and affect the battery's cycle stability and service life.

[0074] Due to the above defects, copper oxide is usually not used as an independent negative electrode material, but as a doping material combined with other materials (such as graphite). The purpose of this is to take advantage of the high capacity of copper oxide and make up for its shortcomings in electrochemical activity and volume stability with the help of the structural stability of other materials.

[0075] In summary, copper oxide has dual properties as a negative electrode material for batteries: on the one hand, it has a high theoretical capacity and potential economic and environmental advantages; on the other hand, its electrochemical activity and volume stability issues limit its application as an independent negative electrode material. Therefore, it is necessary to optimize its performance through material compounding and structural design so that it can play a better role in the battery.

[0076] In the embodiment of the present application, by in-situ electrochemical doping of nano-copper oxide inside the graphite layer, on the one hand, the specific capacity of the graphite is improved, and on the other hand, the conductivity of the material is improved by means of the composite of graphite and copper oxide, and the volume expansion of copper oxide is limited by the stable structure of graphite to improve the cycle stability.

[0077] In the embodiment of the present application, nano copper is in situ doped inside graphite by utilizing the precipitation and redeposition of copper, and nano copper oxide is introduced while removing impurities such as cracked carbon and binder on the graphite surface by subsequent oxidation calcination treatment.

[0078] Battery health state (SOH) is a key indicator for measuring battery power, energy, and charge and discharge power. It is also a direct indication of the increase in battery internal resistance or power attenuation. Inside the battery, copper precipitation is closely related to the increase in internal resistance. The core of the method in the embodiment of the present application is to use SOH detection to evaluate and control the amount of copper doping in graphite, thereby achieving accurate management of the copper content in battery materials.

[0079] In traditional battery recycling technology, initial screening usually relies solely on the internal resistance data of the battery, which often lacks accuracy and pertinence. In contrast, the embodiment of the present application directly regards the SOH test result as the level of copper doping in the battery through the pre-established correspondence between SOH and copper content. This method not only simplifies the screening process, but also improves the accuracy and practicality of the screening results.

[0080] By using the battery health status result (SOH) as a judgment indicator of the relative copper doping amount, the present invention can accurately control the copper doping amount to ensure that it is within the effective range. The advantages of this innovative method are:

[0081] (1) Accuracy: The corresponding relationship between SOH and copper content can directly and easily evaluate the copper doping level of each battery, improving the accuracy of screening.

[0082] (2) Efficiency: The screening process is simplified, complex pretreatment and chemical treatment steps are avoided, and rapid screening is achieved.

[0083] (3) Environmental protection: It reduces the harmful chemicals used in traditional methods and reduces the impact on the environment.

[0084] (4) Economic benefits: By precisely controlling the amount of copper doping, the recycling efficiency and reuse value of battery materials are improved, and the recycling cost is reduced.

[0085] (5) Universality: This method is applicable to different types of retired lithium batteries and has wide applicability.

[0086] In summary, the embodiments of the present application innovatively use SOH as an indicator for determining the amount of copper doping, which not only improves the accuracy of controlling the copper content during battery recycling, but also improves the efficiency and environmental friendliness of the entire recycling process, bringing significant progress to the field of battery recycling technology.

[0087] The method provided in the embodiments of the present application is different from the conventional technical means of using strong oxidizing liquid to remove impurities, and repeatedly calcining to remove impurities and calcining to pack carbon to improve material properties. It minimizes the damage to the graphite interlayer spacing and effectively retains the degree of graphitization of graphite.

[0088] In some embodiments, in step S1, the method for detecting the battery health status result includes:

[0089] Step S11, detecting the target retired lithium battery to obtain the battery internal resistance of the target retired lithium battery at the end of its battery life and the internal resistance of the battery in a current state.

[0090] Step S12, calculating the battery health status result corresponding to the target retired lithium battery according to the battery internal resistance at the end of battery life and the internal resistance of the battery in the current state, as well as the internal resistance of the target retired lithium battery when it leaves the factory.

[0091] As mentioned above, retired lithium batteries are tested to determine their internal resistance (R EOL ) and the internal resistance in the current state (R), and can be further compared with the internal resistance at the factory (R BOL ) calculate and compare together.

[0092] Physical measurements can be made using battery testing equipment, such as an internal resistance tester.

[0093] During the calculation, a specific calculation formula is used to determine the SOH value, which reflects the performance status of the battery relative to a new battery, so that the battery's health status result can be obtained. The result is a percentage value used to evaluate whether the battery is suitable for further processing.

[0094] By calculating the SOH value, it is possible to more accurately determine whether the battery is suitable for graphite and copper recycling, thereby improving the economy and efficiency of the entire recycling process.

[0095] Specifically, the SOH value can be automatically calculated by programming battery testing equipment or using data processing software.

[0096] Then, based on the calculated SOH values, the batteries that meet the preset copper doping conditions are screened out, that is, those batteries with SOH values ​​within a specific range. The batteries suitable for disassembly are selected, which usually have better internal structures and higher copper content.

[0097] Finally, through screening, it can be ensured that only batteries with higher value are further processed, avoiding the disassembly of the screened batteries in poor condition, separating the graphite negative electrode sheets or negative graphite powder, and obtaining the graphite powder before regeneration, which is the basic material for subsequent processing.

[0098] The disassembly and separation process provides raw materials for further processing of graphite and doping of copper oxide, while reducing the impact of waste batteries on the environment.

[0099] The calculation expression of the battery health status result is:

[0100]

[0101] Wherein, SOH represents the battery health status result; R EOL Represents the internal resistance of the battery at the end of its life; R BOL represents the internal resistance of the battery when it leaves the factory; R represents the internal resistance of the battery in its current state.

[0102] In the above formula, the parameters are as follows:

[0103] (1) SOH: Battery health status result, expressed as a percentage. It reflects the battery's current performance status compared to the remaining capacity of a new battery. The higher the SOH value, the closer the battery's status is to a new battery.

[0104] (2)R EOL : Battery internal resistance at the end of battery life. This is the expected internal resistance of the battery at the end of its life, which is usually higher than the internal resistance of a new battery. Reasons for the increase in internal resistance can include battery aging, electrolyte decomposition, or other internal battery problems.

[0105] (3)R BOL : The internal resistance of the battery when it leaves the factory. This is the internal resistance value of the battery when it leaves the factory. It is usually low, indicating the best initial state of the battery.

[0106] (4) R: The internal resistance of the battery in its current state. This is the actual measured internal resistance of the battery in its current state. This value will increase as the battery is used and ages.

[0107] In some embodiments, the step S2, using the battery health status result as the copper doping level to screen the target retired lithium batteries, disassembling and separating the target retired lithium batteries whose battery health status meets the preset copper doping conditions to obtain graphite powder before regeneration, comprises:

[0108] Step S21, obtaining the battery health status result of the target retired lithium battery.

[0109] Step S22, determining whether the battery health status result meets the preset copper doping condition.

[0110] It should be noted that, based on the calculated SOH value, it is determined whether the battery meets the preset copper doping conditions. For example, an SOH value between 65% and 80% is the preset copper doping condition, thereby determining whether the battery is suitable for disassembly and separation.

[0111] By setting the SOH threshold range, batteries suitable for further processing can be screened out to avoid ineffective or costly processing of batteries in poor condition. In this step, the SOH threshold is set, and only batteries that reach the threshold range are processed in the next step.

[0112] Step S23: If yes, the target retired lithium battery that meets the preset copper doping condition is disassembled and separated to obtain the graphite powder before regeneration.

[0113] In the above, the screened batteries are disassembled to separate the graphite negative electrode sheets or negative electrode graphite powder, and the graphite powder before regeneration is obtained, which is the basic material for subsequent processing.

[0114] The disassembly and separation process provides raw materials for further processing of graphite and doping of copper oxide, while reducing the impact of waste batteries on the environment.

[0115] Mechanical disassembly equipment can be used to disassemble the battery and extract the graphite negative electrode material.

[0116] With respect to the preset copper doping conditions, in this embodiment, different situations may be included for corresponding processing.

[0117] Furthermore, the preset copper doping condition is: 65%≤SOH≤80%; wherein SOH represents the battery health status result of the target retired lithium battery.

[0118] In addition, if different types of batteries are used, since different types of batteries have different properties and Cu content levels, the method provided in this embodiment can be specifically analyzed and evaluated according to different situations:

[0119] (1) If the target retired lithium battery is a lithium cobalt oxide battery or a ternary lithium battery, the preset copper doping condition is: 75%≤SOH≤80%.

[0120] (2) If the target retired lithium battery is a lithium iron phosphate battery, the preset copper doping condition is: 65%≤SOH≤80%.

[0121] In the above method in the embodiment of the present application, three different preset copper doping conditions are proposed, which are used to screen retired lithium batteries for extraction of copper oxide graphite composite materials. Each condition is targeted at different types of batteries or different application requirements to ensure that the optimal copper content level can be obtained during the extraction process.

[0122] First, the general preset copper doping condition (65% ≤ SOH ≤ 80%): This condition can be applied to general types of batteries as a general screening standard. It allows a certain degree of battery degradation (minimum SOH is 65%), which helps to include more recyclable batteries, thereby increasing the recycling rate of materials. This range is wide and is suitable for copper content requirements, no special requirements for battery types, and the common use of different types of batteries.

[0123] Secondly, the preset copper doping condition for lithium cobalt oxide batteries or ternary lithium batteries (75% ≤ SOH ≤ 80%): This condition is specifically for lithium cobalt oxide batteries or ternary lithium batteries. These battery types have specific characteristics in battery chemistry and structure, which makes copper doping more effective at higher SOH. By setting a higher SOH lower limit (75%), this condition ensures that the battery is recycled in a better state of health, which helps to improve the quality of recycled materials. This narrow range helps to obtain more consistent copper content levels during the extraction process, which is suitable for applications with specific requirements for copper content.

[0124] Again, the preset copper doping condition of lithium iron phosphate batteries (65% ≤ SOH ≤ 80%): the numerical range can be the same as the general condition. This condition is applicable to lithium iron phosphate batteries because this type of battery can still be effectively doped with copper at a lower SOH. This condition takes into account the chemical stability and cycle life of lithium iron phosphate batteries, allowing the battery to be recycled after it has degraded to a certain extent.

[0125] In the method provided in the embodiment of the present application, different preset copper doping conditions are set for different types of retired lithium batteries based on a comprehensive consideration of the chemical characteristics, cycle life, and the impact of copper content on battery performance of each battery.

[0126] In terms of specific battery types, lithium cobalt oxide batteries and ternary lithium batteries have similar chemical characteristics and show the best copper doping effect in a similar SOH range (75%-80%). This is because the copper content of these two batteries in this health state range has the most significant improvement in battery performance.

[0127] However, due to its unique chemical structure and longer cycle life, lithium iron phosphate batteries can achieve the best copper doping effect in a higher SOH range (such as 65%-80%). This shows that lithium iron phosphate batteries can still maintain good structural stability and electrochemical performance at a higher health state, thus allowing copper doping in a wider SOH range.

[0128] The appropriate amount of copper doping can improve the conductivity and specific capacity of the battery, but excessive copper leads to a decrease in battery performance. The optimal copper content range of different battery types may be different, so different SOH ranges need to be set according to the characteristics of each battery. For details, please refer to the data in Table 4 in Example 1.

[0129] In addition, in addition to the above three types of batteries, other batteries may include but are not limited to lithium manganese oxide batteries, lithium iron manganese phosphate batteries, etc., and the corresponding preset copper doping conditions can be obtained using the method provided in this application (such as the method in Experiment 1), which should also be within the scope of protection of this application.

[0130] In the embodiment of the present application, the battery health state (SOH) is regarded as a method of the copper content of the battery, and the battery is screened as an evaluation criterion based on the close relationship between the internal resistance of the battery and the precipitation and deposition of copper. By detecting SOH, the copper content in the battery can be indirectly evaluated to determine whether it meets the preset copper doping conditions. The advantage of this method is that it can accurately screen out batteries suitable for copper doping, improve the efficiency and quality of material recycling, and reduce the treatment of batteries that are not suitable for copper doping, thereby reducing the recycling cost. In addition, it avoids chemical treatment processes that are harmful to the environment and achieves green recycling. The beneficial effects of this technical solution include improving the electrochemical properties of the battery, such as specific capacity and cycle stability, optimizing the recycling process, improving the consistency and reliability of recycled materials, and increasing the market value of the recycled copper oxide graphite composite material. Therefore, setting different preset copper doping conditions for different batteries and using SOH as an indicator for evaluating the copper content of the battery is not only scientific and reasonable, but also can effectively improve the efficiency and quality of battery recycling, reduce environmental impact, and promote the sustainable development of battery recycling.

[0131] In some embodiments, after determining whether the battery health status result meets the preset copper doping condition in step S22, the method further includes:

[0132] Step S23: If not, perform the following processing according to the battery health status result of the target retired lithium battery:

[0133] (1) If the battery health status result is greater than the maximum value of the preset copper doping condition, the target retired lithium battery is pre-processed, and the process returns to execute step S1 to detect the target retired lithium battery and obtain the battery health status result corresponding to the target retired lithium battery;

[0134] (2) If the battery health status result is lower than the minimum value of the preset copper doping condition, the target retired lithium battery is subjected to harmless treatment.

[0135] As mentioned above, the SOH value of the battery is evaluated to determine whether it meets the preset copper doping conditions (for example, the SOH value is S 最小值 To S 最大值 Based on the assessment results, it is determined whether the battery is suitable for disassembly and separation to extract graphite and copper.

[0136] If the preset copper doping conditions are not met, there may be the following two situations and corresponding treatment methods:

[0137] (1) Case 1: If SOH>S 最大值 , the processing methods include:

[0138] Pre-treatment: Pre-treating the battery, which can include charge-discharge cycling, reverse charging, over-discharge or short-circuit treatment, etc., to improve the health of the battery and prepare for graphite recovery.

[0139] Re-evaluation: After the pre-processing is completed, the system will re-test the health status of the battery to determine whether the battery now meets the preset copper doping conditions. If it meets the conditions, step S23 can be executed for processing. If it does not meet the conditions, it is still necessary to return to step S1 until the preset copper doping conditions are met.

[0140] (2) Case 2: If SOH 最小值 , the processing methods include:

[0141] Harmless treatment: refers to the graphite in the battery has lost its performance and cannot be directly recycled or reused. It can be classified separately and directly subjected to harmless means such as physical disassembly, material separation, or hydrometallurgical recycling to ensure that the harmful substances in the battery are properly handled and valuable materials can be recovered.

[0142] In summary, the corresponding relationship between different battery health status results and different processing methods is shown in Table 1:

[0143] Table 1. Corresponding processing methods for different battery health status results

[0144] NO. SOH Processing 1 <![CDATA[SOH>S 最大值 ]]> Preprocessing + Re-evaluation 2 <![CDATA[S 最小值 ≤SOH≤S 最大值 ]]> Disassembly and separation 3 <![CDATA[SOH<S 最小值 ]]> Harmless treatment

[0145] This step can maximize the use of resources. Through pretreatment, the health of the battery can be improved, making it suitable for further material recycling, thereby maximizing resource utilization. Batteries in poor condition are harmlessly treated to ensure that harmful substances do not pollute the environment, while valuable materials are recovered. Through screening and treatment, expensive material recycling on unsuitable batteries is avoided, thereby reducing overall costs.

[0146] An automated system can be used to evaluate the health status of the battery and automatically decide whether to perform pretreatment or harmless treatment based on the results. Battery pretreatment equipment, such as charge and discharge cycle equipment, can be used to perform necessary pretreatment on the battery.

[0147] Use non-hazardous treatment facilities, such as physical disassembly equipment and material separation systems, to handle batteries in poor condition.

[0148] In some embodiments, in step S23, the preprocessing includes:

[0149] Step S231, at least one of charge-discharge cycle processing, reverse charge processing, over-discharge <1.2V processing and short circuit processing.

[0150] ​As mentioned above, the charge-discharge cycle treatment is to promote the electrochemical reaction inside the battery by subjecting the battery to a series of charge-discharge cycles, especially in the process of copper ions dissolving from the copper foil and migrating to the negative electrode graphite. This cycle treatment helps the deposition of copper ions on the graphite negative electrode and increases the copper content in the graphite.

[0151] The reverse charging treatment mentioned above is to reversely charge the battery, that is, connect the positive and negative electrodes in reverse, and perform a short charge. This treatment can increase the electrochemical stress inside the battery, causing more copper ions to dissolve from the copper foil and migrate to the negative electrode graphite, increasing the copper content in the graphite.

[0152] The above-mentioned over-discharge <1.2V treatment refers to discharging the battery to a voltage lower than 1.2V, which is much lower than the discharge cut-off voltage of the battery. This over-discharge treatment can increase the potential difference inside the battery, promote the dissolution of copper ions from the copper foil and migrate to the negative electrode graphite, thereby increasing the copper content in the graphite.

[0153] Short-circuit treatment: The positive and negative electrodes of the battery are directly contacted through an external circuit to form a short circuit. This treatment can quickly change the electric field distribution inside the battery, promote the dissolution of copper ions from the copper foil and migrate to the negative electrode graphite, and increase the copper content in the graphite.

[0154] In summary, these treatment methods increase the possibility of copper ions dissolving from copper foil and migrating to negative electrode graphite through different electrochemical means, thereby forming more copper-doped graphite in battery materials. This not only improves the copper recovery efficiency, but also provides high-quality raw materials for the subsequent preparation of copper oxide graphite composite materials. Through these methods, copper can be effectively recovered from retired lithium batteries and reused in graphite materials, providing an effective technical approach for battery recycling and material regeneration.

[0155] In some embodiments, in step S23, the disassembly and separation process includes:

[0156] In step S232, one of the following two methods may be included:

[0157] (1) Disassembling the target retired lithium battery to obtain a graphite negative electrode sheet.

[0158] (2) crushing and sorting the target retired lithium batteries to obtain negative electrode graphite powder.

[0159] Step S233, performing solvent washing treatment on the graphite negative electrode sheet or the negative electrode graphite powder to obtain the graphite powder before regeneration.

[0160] In some embodiments, the solvent used in the solvent washing treatment includes at least one of water, carbonate solvents, organic ether solvents and N-methylpyrrolidone.

[0161] In some embodiments, in step S232, the sorting process includes at least one of gravity sorting, magnetic separation and flotation.

[0162] In some embodiments, the step S3, calcining the graphite powder before regeneration to obtain the copper oxide graphite composite material, comprises:

[0163] Step S31, subjecting the graphite powder before regeneration to calcination treatment, airflow classification, demagnetization treatment and mixing treatment in an air atmosphere to obtain the copper oxide graphite composite material.

[0164] As mentioned above, the regenerated graphite powder needs to be calcined, air flow classified, demagnetized and mixed to obtain the final product: copper oxide graphite composite material.

[0165] It should be noted that the final product of the copper oxide graphite composite material obtained in the above steps is theoretically a copper oxide graphite composite material that meets the production requirements. However, in order to ensure that the product meets the requirements, the entire process of the product can be controlled, and the data before and after the raw material extraction can be mastered and compared, a content detection step can be added before obtaining the copper oxide graphite composite material.

[0166] For example, the following steps may be added after the demagnetization treatment and before the mixing treatment, including:

[0167] Step S32, testing the copper content of the product (such as the product after demagnetization treatment) to obtain the copper content result;

[0168] Step S33, mixing the intermediate product whose copper content meets the preset copper content qualification condition to obtain the copper oxide graphite composite material.

[0169] Furthermore, the preset copper content qualification condition is that the copper content is less than 3%, for example, 2.5%, 2.0%, 1.5%, 1.0%, 0.5%, 0.1%, etc.

[0170] As mentioned above, the purpose of detecting the copper content is that the doping of copper oxide can improve the electrochemical properties of graphite, including specific capacity and cycle stability. By controlling the copper content, the electrochemical properties of the material can be optimized, making it more suitable as a negative electrode material for the battery. Copper is a good conductive material, but its excessive doping may affect the safety performance of the battery. By detecting and controlling the copper content, battery safety problems caused by excessive copper content can be avoided. By precisely controlling the copper content, unnecessary material waste can be avoided, thereby improving material utilization and cost-effectiveness. Controlling the copper content helps reduce the use of unnecessary chemicals, thereby reducing the impact on the environment.

[0171] The preset copper content qualification condition is to ensure that the final product meets specific performance requirements and quality standards. This condition is set based on a comprehensive consideration of battery performance, safety and cost-effectiveness. By setting an upper limit on the copper content, excessive doping can be avoided. Excessive copper doping will reduce the conductivity and cycle stability of the material and affect battery performance. Excessive copper content may increase the risk of internal short circuits in the battery and affect battery safety.

[0172] In short, the purpose of testing the copper content of the intermediate products and setting the preset copper content qualification conditions is to ensure the performance, safety, cost-effectiveness and environmental friendliness of the copper oxide-graphite composite materials, while meeting the requirements of the market and regulations. This step is a key link in quality control during the material preparation process.

[0173] In some embodiments, the calcination temperature of the calcination treatment is 450° C. to 800° C. For example, the minimum temperature may be 450° C., 500° C., 550° C., 600° C., 650° C., 700° C., 750° C., 800° C., etc. For example, in a preferred embodiment, the calcination temperature of the calcination treatment is 600° C.

[0174] In some embodiments, the calcination time of the calcination treatment is 1 hour to 2 hours. For example, the calcination time can be 1 hour, 1.5 hours, 2 hours, etc.

[0175] A copper oxide-graphite composite material is also provided in an embodiment of the present application, which is prepared by the copper oxide-graphite composite material extraction method as described in any one of the above embodiments.

[0176] The present application also provides a copper oxide graphite composite material in an embodiment, which is prepared by the copper oxide graphite composite material extraction method as described in the above embodiment.

[0177] The present application also provides a negative electrode in an embodiment, wherein the negative electrode comprises a negative electrode material;

[0178] The negative electrode material is the copper oxide graphite composite material as described in the above embodiment.

[0179] A battery is also provided in an embodiment of the present application, comprising the negative electrode as described in the above embodiment.

[0180] An embodiment of the present application also provides an electrical device, including the battery described in the above embodiment.

[0181] As mentioned above, electrical equipment can include many types, covering (including but not limited to) from portable electronic devices such as smartphones, tablets, laptops, cameras and music players, to wearable devices such as smart watches, health trackers and virtual reality helmets. Household appliances such as vacuum cleaners, rice cookers, refrigerators, washing machines, air conditioners and microwave ovens are also common categories of electrical equipment. In addition, personal care devices include electric toothbrushes, shavers, hair dryers and massagers. Power tools such as electric drills, electric saws, sanders and cutters, as well as electric vehicles (including BEV, PHEV and HEV), electric bicycles and electric scooters are also part of electrical equipment. Drones are used in fields such as photography, monitoring and logistics distribution, while medical devices such as pacemakers, hearing aids and medical monitoring devices are also important electrical equipment. Industrial equipment such as automated production lines, robots and control systems, communication base stations to provide power for mobile phone networks and other wireless communication networks, solar energy storage systems to store electricity generated by solar power, emergency power and backup power systems such as uninterruptible power supplies (UPS) and emergency lighting systems, and energy storage power stations for balancing grid loads and storing renewable energy are all important components of electrical equipment.

[0182] These electrical devices usually require batteries as an energy source, and the batteries described in the embodiments of the present application can be widely used in the above-mentioned devices due to their high capacity and good cycle stability, providing long-lasting and reliable power support.

[0183] The present invention is further described below by means of specific examples, but it should be understood that these examples are only used for more detailed description and should not be construed as limiting the present invention in any form.

[0184] Experiment 1: Establishing and examining the corresponding relationship

[0185] In this experiment, the corresponding relationship between the battery health status result SOH and the copper content was investigated.

[0186] Experimental methods:

[0187] (1) A large number of samples were selected for the three types of batteries, namely, lithium cobalt oxide battery (A), lithium iron phosphate battery (B), and ternary lithium battery (C), to detect and calculate the battery health status results and obtain the corresponding SOH values.

[0188] (2) According to the SOH value, it is divided into 6 levels, as shown in Table 2:

[0189] Table 2. SOH value classification

[0190] Gear 1 2 3 4 5 6 SOH ≤60 65≥SOH>60 75≥SOH>65 80≥SOH>75 95≥SOH>80 100≥SOH>95

[0191] (3) Each type of battery (3 types) is screened according to 6 grades (as shown in Table 2), and is required to meet the following requirements at the same time:

[0192] A. The SOH value of each SOH range of each battery screened out conforms to the normal distribution;

[0193] B. The SOH value of each SOH level of each screened battery includes at least one middle value, a maximum value, and a minimum value of the SOH range;

[0194] C. The number of battery samples in each SOH level of each screened battery is 35.

[0195] In this experiment, Python programming language is used, combined with functions in Pandas and SciPy libraries, to implement the data screening process by stratifying and grouping the battery test data, normality test and special value assurance algorithm. In addition, data screening can also be performed through R, MATLAB or professional statistical software (such as SPSS or SAS).

[0196] (4) All batteries in different SOH levels of different battery types are carefully disassembled to obtain graphite negative electrodes, and the graphite negative electrodes are solvent washed, dried, and sieved to obtain graphite powder. The graphite powder is digested with aqua regia to obtain a solution, and the solution is detected using an inductively coupled plasma spectrometer (ICP-OES) to obtain the copper content result.

[0197] (5) Statistical results are obtained for all copper content results.

[0198] Table 3. Statistical results

[0199]

[0200] In the table, A, B and C represent lithium cobalt oxide batteries, lithium iron phosphate batteries and ternary lithium batteries respectively.

[0201] The 95% confidence interval of Cu content corresponding to each SOH level of each battery is calculated according to the formula. Formula:

[0202]

[0203] in, represents the sample mean. t is the t value corresponding to the 95% confidence level and degrees of freedom (df = n-1). s is the sample standard deviation. n is the total number of samples.

[0204] Experimental results:

[0205] Table 4. 95% confidence interval of Cu content for each SOH level of each battery

[0206] NO. SOH gear range % A B C 1 100-95 ≤0.1 ≤0.1 ≤0.1 2 95-80 0.1-0.7 0.1-0.5 0.1-0.7 3 80-75 0.7-1.8 0.5-1.5 0.7-1.7 4 75-65 1.8-2.7 1.5-1.9 1.7-2.5 5 65-60 2.7-3.5 1.9-2.5 2.5-3.2 6 ≤60 ≥3.5 ≥2.5 ≥3.2

[0207] In the table, A, B, and C represent lithium cobalt oxide batteries, lithium iron phosphate batteries, and ternary lithium batteries, respectively.

[0208] analyze:

[0209] Referring to the data in Table 4, based on the corresponding relationship between copper content and battery health status (SOH%), the preset copper doping conditions for different types of batteries can be determined.

[0210] It should be noted that when the copper content is within the range of 0.7% to 1.8%, the electrochemical performance of the battery reaches a relatively optimal state. Therefore, in this embodiment, this copper content range is regarded as an ideal interval of the preset copper doping conditions.

[0211] By analyzing the data in Table 4, it can be found that when the SOH% of lithium cobalt oxide battery (A) and ternary lithium battery (C) is 80%-75%, the copper content falls within the range of 0.7% to 1.8%; and when the SOH% of lithium iron phosphate battery (B) is 85%-65%, the copper content is also in this optimal range.

[0212] Therefore, the specific preset copper doping conditions are: the SOH% preset conditions for lithium cobalt oxide batteries (A) and ternary lithium batteries (C) are 80%-75%, and the SOH% preset conditions for lithium iron phosphate batteries (B) are 80%-65%. These conditions are used as evaluation criteria to screen retired lithium batteries suitable for copper oxide graphite composite material extraction to ensure the efficiency of the recycling process and the quality of the materials.

[0213] It should be noted that in order to ensure the statistical validity of the analysis, this experiment conducted a normality test on the copper content data of each SOH level. The Shapiro-Wilk test was used to evaluate the normal distribution of the data. The normality test results of all data sets met the prerequisites for statistical analysis, ensuring the validity of the subsequent confidence interval calculation using the t distribution.

[0214] In order to reduce the impact of outliers on the experimental results, this experiment used a box plot to detect outliers in the data of all SOH gears. After evaluation, the identified outliers were decided whether to be excluded to ensure the robustness of the data analysis.

[0215] The data of marginal gears (such as SOH ≤ 60%) are greatly affected by the sample size and data distribution characteristics. Therefore, in this experiment, enhanced statistical analysis of the data of this gear was performed, including the use of non-parametric methods (such as Mann-Whitney U test) to supplement the t-test to ensure the wide applicability and accuracy of the analysis results.

[0216] This experiment used a series of statistical methods and data processing strategies to ensure the reliability and validity of the results. Normality tests, outlier processing, and special consideration of marginal data together ensure the scientificity and reliability of the experimental results. In addition, all statistical analyses were performed using appropriate software tools to ensure the transparency and repeatability of the analysis process.

[0217] Experiment 2: Investigation of extraction methods

[0218] 1. Embodiment 1

[0219] In this example, an experiment was conducted to regenerate a copper oxide-graphite composite material from waste lithium-ion batteries.

[0220] Target retired lithium batteries: lithium cobalt oxide batteries;

[0221] Experimental methods:

[0222] (1) First, the target retired lithium battery is subjected to a battery health state (SOH) test and is calculated using Formula 1 to obtain a battery health state result SOH=81%.

[0223] According to Table 1 and Table 4, the battery is placed in a discharge cabinet for pretreatment. In this embodiment, an over-discharge treatment is performed to discharge to 0.5V, and then the SOH test is performed again. The battery health status result SOH=80%.

[0224] (2) The battery with SOH=80% described in step (1) is finely disassembled to obtain a graphite negative electrode sheet, and the graphite negative electrode sheet is washed with distilled water to obtain graphite powder before regeneration.

[0225] (3) calcining the graphite powder before regeneration described in step 2 at 600° C. for 1 hour in an air atmosphere, and then performing air flow classification treatment and demagnetization treatment;

[0226] (4) The copper content of the product was detected to be 0.91%, thereby obtaining a regenerated copper oxide-graphite composite material.

[0227] The obtained copper oxide-graphite composite material was subjected to XRD diffraction test and SEM test, and the results are as follows: Figure 2 and Figure 3 shown.

[0228] 2. Embodiment 2

[0229] In this example, an experiment was conducted to regenerate a copper oxide-graphite composite material from waste lithium-ion batteries.

[0230] Target retired lithium batteries: lithium cobalt oxide batteries;

[0231] Experimental methods:

[0232] (1) First, the target retired lithium battery is subjected to a battery health state (SOH) test, and the battery health state result SOH=75% is calculated using Formula 1; Table 1 and Table 4 determine that the preset copper doping conditions are met.

[0233] (2) finely disassembling the battery with SOH=75% described in step (1) to obtain a graphite negative electrode sheet, and washing the graphite negative electrode sheet with distilled water to obtain graphite powder before regeneration;

[0234] (3) calcining the graphite powder before regeneration described in step (2) at 600° C. for 1 hour in an air atmosphere, and then performing air flow classification treatment and demagnetization treatment;

[0235] (4) The copper content of the product was detected to be 1.76%, thereby obtaining a regenerated copper oxide-graphite composite material.

[0236] 3. Embodiment 3

[0237] In this example, an experiment was conducted to regenerate a copper oxide-graphite composite material from waste lithium-ion batteries.

[0238] Target retired lithium batteries: ternary lithium batteries;

[0239] Experimental methods:

[0240] It is basically the same as Example 1, except that the battery health status result SOH=73%;

[0241] The copper content of the tested product is 1.79%.

[0242] 3. Embodiment 4

[0243] In this example, an experiment was conducted to regenerate a copper oxide-graphite composite material from waste lithium-ion batteries.

[0244] Target retired lithium batteries: lithium iron phosphate batteries;

[0245] Experimental methods:

[0246] Basically the same as Example 1, except that the battery health status result SOH=67%;

[0247] The copper content of the tested product is 1.81%.

[0248] 4. Comparative Example 1

[0249] In this comparative example 1, an experiment was conducted to regenerate a copper oxide-graphite composite material from waste lithium-ion batteries.

[0250] Target retired lithium batteries: lithium cobalt oxide batteries;

[0251] Experimental methods:

[0252] (1) First, a retired lithium-ion battery is tested for its state of health (SOH), and the test result shows that SOH = 78%;

[0253] (2) finely disassembling the battery with SOH=78% described in step (1) to obtain a graphite negative electrode sheet, and washing the graphite negative electrode sheet with distilled water to obtain graphite powder before regeneration;

[0254] (3) calcining the graphite powder before regeneration described in step (2) at 400° C. for 1 hour in an air atmosphere, and then performing air flow classification treatment and demagnetization treatment;

[0255] (4) The copper content of the product was detected to be 1.12%, and regenerated graphite powder was obtained.

[0256] The obtained copper oxide-graphite composite material was subjected to XRD diffraction test, and the results were as follows: Figure 4 shown.

[0257] 5. Comparative Example 2

[0258] In this comparative example 2, an experiment was conducted to regenerate a copper oxide-graphite composite material from waste lithium-ion batteries.

[0259] Target retired lithium battery: the same as the lithium cobalt oxide battery in Example 1;

[0260] Experimental methods:

[0261] The graphite powder before regeneration obtained in step (2) of Example 1 was added with 0.1 mol of sulfuric acid and 0.1 mol of hydrogen peroxide at a solid-liquid ratio of 1:4, and the mixture was stirred for reaction for 2 h. The acid-leached graphite powder was obtained after washing and drying. The copper content in the acid-leached graphite powder was found to be 0.01%, and its electrochemical properties were tested.

[0262] 6. Comparative Example 3

[0263] In this comparative example 3, an experiment was conducted to regenerate a copper oxide-graphite composite material from waste lithium-ion batteries.

[0264] Target retired lithium batteries: lithium cobalt oxide batteries;

[0265] Experimental methods:

[0266] (1) First, a retired lithium-ion battery is tested for its state of health (SOH). Formula 1 is used to calculate the test result, and the SOH is 61%;

[0267] (2) finely disassembling the battery with SOH=61% described in step (1) to obtain a graphite negative electrode sheet, and washing the graphite negative electrode sheet with distilled water to obtain graphite powder before regeneration;

[0268] (3) calcining the graphite powder before regeneration described in step (2) at 600° C. for 1 h in an air atmosphere, and then performing air flow classification treatment and demagnetization treatment;

[0269] (4) The copper content was detected to be 3.12%, and a regenerated copper oxide-graphite composite material was obtained.

[0270] 7. Horizontal test experiments, results and analysis:

[0271] 1. Test method:

[0272] (1) Sample preparation: The copper oxide-graphite composite material prepared in the embodiment and the comparative example is made into a battery electrode, the material is mixed with a conductive agent and a binder, and coated on a copper foil.

[0273] (2) Battery assembly: Assemble the prepared electrodes with other battery components (metal lithium, separator, electrolyte) into a half-cell.

[0274] (3) Electrochemical testing: Use a battery testing system to perform charge and discharge tests and record the charge and discharge curves and capacity data.

[0275] (4) Data analysis: Analyze test data and evaluate the electrochemical properties of the material, including specific capacity, coulombic efficiency, cycle stability, etc.

[0276] 2. Test results and analysis:

[0277] Table 5. Electrical properties of graphite before and after regeneration at 0.1C in the examples and comparative examples

[0278]

[0279] Table 5 provides the data of the charge-withdrawal performance of the graphite material before and after regeneration at a current density of 0.1C, including the first charge specific capacity, the first discharge specific capacity, the first coulombic efficiency, and the capacity retention rate after 100 cycles of 1C. Among them, the data corresponding to "before regeneration" in the material name represents the charge-withdrawal performance data of the graphite powder before regeneration in Example 1.

[0280] These data can be used to evaluate the impact of recycling on the properties of graphite materials.

[0281] Based on the results of the first discharge specific capacity and the first charge specific capacity, it can be seen that the lower first charge and discharge specific capacity in the graphite before regeneration indicates that the performance of the original graphite material in the battery has degraded. Examples 1 to 2 both show significantly higher charge and discharge specific capacities, indicating that the method in this embodiment effectively improves the electrochemical performance of the material. Although the comparative example also has a higher specific capacity, the improvement is smaller than that of the present technology, showing the advantages of the present technology in improving material performance.

[0282] In terms of the initial coulombic efficiency, the coulombic efficiency of the graphite before regeneration is low, indicating that there is a lot of charge loss during the initial charge and discharge process. The coulombic efficiency of the embodiment is high, indicating that the technical method effectively improves the charge transfer efficiency and reduces the charge loss. Although the comparative example also has a high coulombic efficiency, the improvement effect is not obvious compared with the technical method, which further proves the effectiveness of the technology.

[0283] In terms of the capacity retention rate after 100 cycles of 1C, the capacity retention rate of graphite before regeneration is low, indicating that the performance of the material is seriously degraded during the cycle. The embodiment shows a higher capacity retention rate, indicating that the technical method effectively improves the cycle stability of the material. Although the capacity retention rate of the comparative example is higher, the improvement effect is limited compared with the method used in this embodiment, which once again emphasizes the superiority of this technology.

[0284] By comparing the electrochemical performance data of the graphite material before and after regeneration, it can be clearly seen that the method used in the embodiment of the present application has significant advantages in improving the first charge specific capacity, the first discharge specific capacity, the first coulombic efficiency and the cycle stability of the material. Compared with the comparative example, the method in this embodiment not only improves the performance of the material, but also ensures the stability of the material in the recycling use, thereby proving its effectiveness and superiority in battery material recovery and reuse. These results support the practicality of the method in this application and its potential in practical applications.

[0285] Table 6. Performance results of the embodiments

[0286] Material Name Interlayer spacing d002 / nm Graphitization degree / % Before regeneration 0.33615 91.20 Example 1 0.33664 85.55 Example 2 0.33674 84.38

[0287] Referring to the data in Table 6, the effects of the regeneration treatment on the graphite interlayer spacing and the degree of graphitization based on the materials in Examples 1 and 2 are shown, in order to compare the structural changes of the graphite materials before and after regeneration.

[0288] The data show that the interlayer spacing of graphite after regeneration has increased slightly, but the change is not significant, which indicates that the regeneration process effectively maintains the layered structure of graphite. At the same time, the degree of graphitization has decreased, but the decrease is small, indicating that the regeneration process has limited damage to the crystallinity of graphite while improving the electrochemical properties of the material.

[0289] This result shows that the method in the embodiment of the present application has achieved a balance in optimizing the performance of graphite materials, which not only improves the electrochemical performance of the material, but also better preserves the structural integrity of graphite. The performance of recycled graphite materials in battery applications proves the potential application value of the method in the embodiment of the present application in actual battery production, especially in improving battery performance and reducing costs, and provides a strong experimental basis for further research and development of battery materials based on recycled graphite.

[0290] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. However, these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for extracting a copper oxide graphite composite material, characterized in that: include: Detecting a target retired lithium battery to obtain a battery health status result corresponding to the target retired lithium battery; The target retired lithium batteries are screened by using the battery health status results as the copper doping level, and the target retired lithium batteries whose battery health status meets the preset copper doping conditions are disassembled and separated to obtain graphite powder before regeneration; The graphite powder before regeneration is calcined to obtain a copper oxide graphite composite material.

2. The method for extracting copper oxide graphite composite material according to claim 1, characterized in that: The method for detecting the battery health status result includes: Detecting the target retired lithium battery to obtain the battery internal resistance of the target retired lithium battery at the end of its battery life and the internal resistance of the battery in a current state; Calculate the battery health status result corresponding to the target retired lithium battery according to the battery internal resistance at the end of battery life and the internal resistance of the battery in the current state, as well as the internal resistance of the target retired lithium battery when it leaves the factory; Preferably, the calculation expression of the battery health status result is: Wherein, SOH represents the battery health status result; R EOL Represents the internal resistance of the battery at the end of its life; R BOL represents the internal resistance of the battery when it leaves the factory; R represents the internal resistance of the battery in its current state.

3. The method for extracting copper oxide graphite composite material according to claim 1, characterized in that: The method of using the battery health status result as the copper doping level to screen the target retired lithium batteries, and disassembling and separating the target retired lithium batteries whose battery health status meets the preset copper doping conditions to obtain graphite powder before regeneration includes: Obtaining the battery health status result of the target retired lithium battery; Determining whether the battery health status result meets the preset copper doping condition; If yes, the target retired lithium battery meeting the preset copper doping condition is disassembled and separated to obtain the graphite powder before regeneration; Preferably, the preset copper doping condition is: 65%≤SOH≤80%; wherein SOH represents the battery health status result of the target retired lithium battery; Preferably, if the target retired lithium battery is a lithium cobalt oxide battery or a ternary lithium battery, the preset copper doping condition is: 75%≤SOH≤80%; Preferably, if the target retired lithium battery is a lithium iron phosphate battery, the preset copper doping condition is: 65%≤SOH≤80%.

4. The method for extracting copper oxide graphite composite material according to claim 3, characterized in that: After determining whether the battery health status result meets the preset copper doping condition, the method further includes: If not, the following processing is performed according to the battery health status result of the target retired lithium battery: If the battery health status result is greater than the maximum value of the preset copper doping condition, the target retired lithium battery is pre-processed, and the step of returning to execute the step of detecting the target retired lithium battery to obtain the battery health status result corresponding to the target retired lithium battery; If the battery health status result is lower than the minimum value of the preset copper doping condition, the target retired lithium battery is subjected to harmless treatment; Preferably, the pre-treatment includes at least one of charge-discharge cycle treatment, reverse charge treatment, over-discharge <1.2V treatment and short-circuit treatment.

5. The method for extracting copper oxide graphite composite material according to claim 3, characterized in that: The disassembly and separation process comprises: Disassembling the target retired lithium battery to obtain graphite negative electrode sheets; or crushing and sorting the target retired lithium battery to obtain negative electrode graphite powder; Performing solvent washing treatment on the graphite negative electrode sheet or the negative electrode graphite powder to obtain the graphite powder before regeneration; Preferably, the solvent used in the solvent washing treatment includes: at least one of water, carbonate solvents, organic ether solvents and N-methylpyrrolidone; Preferably, the separation process includes at least one of gravity separation, magnetic separation and flotation.

6. The method for extracting the copper oxide-graphite composite material according to claim 1, characterized in that: The method of calcining the graphite powder before regeneration to obtain a copper oxide graphite composite material comprises: The graphite powder before regeneration is subjected to calcination treatment, airflow classification, demagnetization treatment and material mixing treatment respectively under air atmosphere to obtain the copper oxide graphite composite material; Preferably, the calcination temperature of the calcination treatment is 450°C to 800°C; Preferably, the calcination time of the calcination treatment is 1 hour to 2 hours.

7. A copper oxide graphite composite material, characterized in that: The copper oxide graphite composite material is prepared by the extraction method according to any one of claims 1 to 6.

8. A negative electrode, characterized in that The negative electrode includes a negative electrode material; The negative electrode material is the copper oxide graphite composite material as claimed in claim 7.

9. A battery, characterized in that: Comprising the negative electrode as claimed in claim 8.

10. An electrical equipment, characterized in that: Comprising the battery as claimed in claim 9.